Combined primary carnitine deficiency with neonatal intrahepatic cholestasis caused by citrin deficiency in a Chinese newborn - Yiming Lin; Weihua Lin; Yanru Chen; Chunmei Lin; Zhenzhu Zheng; Jianlong Zhuang; Qingliu Fu (BMC, 2020)
Abstract Background Primary carnitine deficiency (PCD) is an autosomal recessive disorder affecting the carnitine cycle and resulting in defective fatty acid oxidation. Neonatal intrahepatic cholestasis caused by citrin deficiency (NICCD) is an autosomal recessive disorder and one of the main causes of inherited neonatal cholestasis. Both PCD and NICCD are included in the current expanded newborn screening (NBS) targets. Case presentation Targeted exome sequencing was performed on a Chinese proband, and Sanger sequencing was utilised to validate the detected mutations. The patient who was initially suspected to have PCD based on the NBS results presented with neonatal intrahepatic cholestasis and ventricular septal defect. Further investigations not only confirmed PCD but also revealed the presence of NICCD. Four distinct mutations were detected, including c.51C > G (p.F17L) and c.760C > T (p.R254X) in SLC22A5 as well as c.615 + 5G > A and IVS16ins3kb in SLC25A13. Conclusions This is the first reported case of PCD and NICCD occurring in the same patient. The dual disorders in a newborn broaden our understanding of inherited metabolic diseases. Thus, this study highlighted the importance of further genetic testing in patients presenting with unusual metabolic screening findings.